The role of various forms of subjective well-being with quality of work life in the aviation industry - Agarwal Shivani; Mewarfarosh Rekha; Solanki Vijender Kumar (Journal of Economics and Management)
Aim/purpose – This study explores the crucial link between the quality of work life (QWL) and subjective well-being (SWB) among aviation industry employees. By delving into the current state of QWL and its relationship with key aspects of SWB, such as life satisfaction, positive affect, and negative affect, this research aims to offer valuable insights that can help employee well-being and job satisfaction in the aviation industry.